Etiologies, trends, and predictors of 30‐day pediatric readmissions after hospitalizations for diabetic ketoacidosis in the United States. Issue 6 (16th June 2020) - Bhatt, Parth; Dave, Mihir; Amponsah, Jason K.; Jain, Apurva; Yagnik, Priyank; Asare‐Afriyie, Barbara; Donda, Keyur; Sharma, Mayank; Parmar, Narendrasinh; Patel, Achint; Bhatt, Neel; Lunsford, Alison J.; et al.
Abstract: Objective: To determine the causes, predictors, and trends of 30‐day readmissions following hospitalizations for pediatric diabetic ketoacidosis (DKA) in the United States (US) from 2010 to 2014. Research design and methods: We used International Classification of Diseases, ninth revision, Clinical Modification codes to identify children with DKA aged 2 to 18 years from the National Readmission Database in the US. Patients who had readmission within 30 days after an index admission for DKA were included in the study. We combined similar diagnoses into clinically important categories to determine the cause of readmission. The primary outcome was all‐cause 30‐day (AC30) readmissions. Categorical and continuous variables were analyzed using chi‐square or student's t ‐test or Wilcoxon rank sum tests respectively. We performed multivariable logistic regression to identify predictors of 30‐day readmission. Results: From 2010 through 2014, a weighted total of 87 815 index DKA‐related pediatric hospitalizations were identified of which, 4055 patients (4.6%) had AC30 readmissions and this remained unchanged during the study period. Of all the readmissions, 69% were attributed to DKA. In multivariable regression analysis, the odds of AC30 readmission and 30‐day readmission attributed to DKA alone were increased for females, adolescents, patients with depression and psychosis, and discharge against medical advice, while private insurance, the highest income quartile, and admission at teaching hospitals were associated with lower odds of AC30 readmission and 30‐day readmission attributed to DKA only. Conclusion: We identified several factors associated with readmission after hospitalization for DKA. Addressing these factors such as depression may help lower readmissions after an admission for DKA.